An Introduction to design and culture 1900 to the present - Sparke, Penny (Routledge, 2020)
Provides a comprehensive guide to the changing relationships between design and culture from 1900 to the present day with an emphasis on five main themes: design and consumption, design and technology, the design profession, design theory, design and identities.